Anxiety Reduction and Improved Concentration in Schoolchildren through Wingwave® Coaching - Frank P. G. Weiland; Marco Rathschlag; Stefanie Klatt (Children, 2021)
(1) Background: For nearly 20 years, the wingwave® method, which combines elements of eye movement desensitization and reprocessing (EMDR) and a muscular strength test, has been used to reduce anxiety and improve relaxation in subjects. Past studies have scientifically evaluated this method in various contexts and have found it to be effective. In this study, we investigated the effects of short-term wingwave® coaching on specific anxiety parameters regarding school, concentration ability, and subjective feelings towards two self-chosen themes in schoolchildren. (2) Methods: A group of 53 schoolchildren aged 11 to 12 years were randomly divided between an experimental and a control group. The experimental group received an intervention of three wingwave® coaching sessions (one hour each). In these sessions, past and present negative feelings towards school as well as psychological resources to face future tasks in school were focused on and utilized. (3) Results: The results showed that the overall text anxiety, manifested anxiety, and dislike of school decreased significantly in the experimental group after the three coaching sessions compared to the control group. Furthermore, both concentration ability and the subjective feeling towards self-chosen subjects improved significantly in the experimental group compared to the control group. (4) Conclusions: Our results indicate that the wingwave® method is an appropriate and effective instrument to reduce school anxiety and to improve concentration performance in schoolchildren—at least in the short and medium term.